Covid and Couvade: Agnotological Beliefs about covid-19 in the Light of the Epidemiology of Ideas (Research, Society and Development, 2022)
Anti-factual and anti-scientific beliefs about the covid-19 pandemic have spread widely in Brazil in the form of an epidemic of ideas in the sense of Dan Sperber. Many of these beliefs were propagated or endorsed in the President of the Republic's speech. In this sense, we analyze the manifest and latent meanings of 200 statements by the President that were considered false or distorted by fact checking vehicles and analyze the propagation of the underlying beliefs in society in the light of Sperber's considerations.  In particular, we draw a parallel between two anti-scientific beliefs: the belief in the usefulness of the couvade (widespread in civilizations of pre-Columbian origin) and the belief in the effectiveness of the “covid kit” (a combination of medical drugs that have scientifically shown to be ineffective) in the prevention and treatment of covid-19, which can be classified as agnotological, given the wide diffusion of scientific knowledge in our modern society. Finally, we make some considerations about the potential for the continued propagation or cognitive erosion of such agnotological beliefs.